The phenomenon of mercy „a ray of strong final divine grace” in the light of the Diary of St. Faustina Kowalska - Rachwalik, Walter (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
Man lives and dies only once. The human race is united by the search for an answer to the question of both the moment of death itself and if - „what” - will follow? God assures the faithful of the existence of eternal life in one of two forms: salvation or damnation. Lord Jesus, King of Mercy, in private revelations given to St. Faustina Kowalska, he confirmed the immutability of God’s judgments in the matter of man’s final things: his temporality and eternity „is a one-off event”.